Financial development institutions and economic growth in the selected Asean-3 countries - Muhammad Sodbir, Hamzah (2022)
The effect of financial development on economic growth is still a debatable issue leading researchers to engage in studying the contributing indicators and extension of the effect. Two commonly used sectors in representing financial development are banking sectors and stock markets. However, institutions are also a factor that influences financial development and economic growth. Previous outcomes differ between countries because of unique institutional quality in term of corruptions level, government bureaucracy, law and order, and risk of investment. Thus, this study investigates the relationship between financial development and economic growth for the selected ASEAN-3 countries, namely Malaysia, Singapore and Thailand for the period of 1984 to 2018 and pay particular attention to institutions' role in affecting the relationship. Autoregressive distributed lag (ARDL) is used in examining the data. The findings indicate that financial development and institutions are significant for all ASEAN-3 countries' economic growth. However, the results for the threshold analysis depict that Malaysia and Singapore possess an inverted U-shape relationship between financial development and economic growth, while Thailand indicates a linear relationship. Hence, increasing financial development beyond the threshold value would provide a negative effect on the economic growth for Malaysia and Singapore. When the interaction is inserted, financial development, banking sectors development, and stock markets development indicate a positive and significant economic growth effect. As indicators for stocks markets are decomposed, the results also show a more significant coefficient after the interaction. It implies the importance of institutions in boosting the effect of financial development on economic growth. So, policies should be outlined by the ASEAN-3 countries to increase and balance the efficiency of the banking sectors and stock markets and to improve institutional quality by reducing the corruption level and increase investment securities through fortification of law and order.